2017
DOI: 10.1016/j.jviromet.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pseudovirus based assay for measuring neutralizing antibodies against coxsackievirus B5

Abstract: Coxsackievirus B5 (CV-B5), an important Coxsackie B virus from genus Enteroviruse within the family Picornaviridae, has also been isolated from Hand, Foot, and Mouth Disease (HFMD) patients, and often associated with neurological manifestations. In this study, we found out that Coxsackievirus B3 (CV-B3) replicon RNA could be encapsidated with CV-B5 capsid to assemble infectious CV-B5 pseudovirus. We then utilized this single round infection system of CV-B5 to develop a neutralizing antibody quantification assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…In our previous work, we have proposed that some enteroviruses may share similar determinants in virion assembly. 25 Our findings in this study further suggest that the enteroviruses within the same genotype group are more likely to have encapsidation compatibility with each other.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In our previous work, we have proposed that some enteroviruses may share similar determinants in virion assembly. 25 Our findings in this study further suggest that the enteroviruses within the same genotype group are more likely to have encapsidation compatibility with each other.…”
Section: Discussionsupporting
confidence: 61%
“…26 Previously, we had found that capsid proteins from CV-A16 could package EV-A71 replicon into infectious CV-A16 pseudovirus, and capsid proteins from CV-B5 could package CV-B3 replicon RNA into infectious CV-B5 pseudovirus. 25 In this work, we showed another successful application of the trans-encapsidation strategy to produce infectious CV-A6 pseudovirus. EV-A71 and CV-A16 replicon both could be encapsidated with CV-A6 capsid to produce CV-A6 pseudovirus; however, CV-B3 and CV-B5 replicon RNA could not be encapsidated with CV-A6 capsid.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[16][17][18][19] Our research group has already constructed numerous types of pseudoviruses relevant to HFMD, including pseudoviruses of enterovirus 71 (EV-A71), CV-A16, CV-B3, CV-B5, and CV-A6, which were used in the development of a pNT assay. [20][21][22][23][24] Here, we report the successful construction of a CV-A10 pseudovirus, and development of a CV-A10 pNT to detect the titre of anti-CV-A10 NtAb. The method was validated using 67 clinical serum samples, and the performance and safety were compared to those of the traditional cNT method.…”
Section: Introductionmentioning
confidence: 99%